The Reduviidae (Hemiptera: Heteroptera) of Alabama, with a morphological key to species - Clem, C.scott; Swanson, Daniel R.; Ray, Charles H. (Zootaxa, 2019)
Alabama is one of the most speciose states in the United States, yet many common groups of organisms, including assassin bugs (Hemiptera: Heteroptera: Reduviidae), have yet to be fully documented. The purpose of this manuscript is to identify all known assassin bug species occurring in the state using literature records and specimens from natural history collections, most notably the Auburn University Museum of Natural History Entomology Collection, to provide new state records, a checklist, and a morphological species key of the Alabama Reduviidae. All total, 61 species within 36 genera and 10 subfamilies are reported from Alabama. Additionally, 40 new state literature records are documented: 34 from Alabama and six from other states.